A Review on the Ethnopharmacology and Phytochemistry of the Neotropical Sages (Salvia Subgenus Calosphace; Lamiaceae) Emphasizing Mexican Species - Ortiz-Mendoza, Nancy; Aguirre-Hernández, Eva; Fragoso-Martínez, Itzi; González-Trujano, María Eva; Basurto-Peña, Francisco A.; Martínez-Gordillo, Martha J. (Frontiers in Pharmacology, 2022)
Salvia is the most diverse genus within the mint family (Lamiaceae), many of its species are well-known due to their medicinal and culinary uses. Most of the ethnopharmacological and phytochemical studies on Salvia are centred in species from the European and Asian clades. However, studies about the most diverse clade, the Neotropical sages (Salvia subgenus Calosphace; 587 spp.), are relatively scarce. This review aims to compile the information on the traditional medicinal uses, pharmacological and phytochemistry properties of the Neotropical sages. To do so, we carried out a comprehensive review of the articles available in different online databases published from the past to 2021 (i.e., PubMed, Scopus, and Web of Science, among others) and summarized the information in tables. We generated presence-absence matrices for four different groups of metabolites (mono-, sesqui-, di-, and triterpenes) to perform ancestral state reconstruction analyses to uncover any phylogenetic patterns in the distribution of such metabolites. We found several studies involving Mexican species of Salvia, but only a few about taxa from other diversity centres. The main traditional uses of the Mexican species of Calosphace are medicinal and ceremonial. In traditional medicine 54 species are used to treat diseases from 15 categories according to the WHO. Pharmacological studies reveal a wide range of biological properties (e.g., antinociceptive, anti-inflammatory, anxiolytic, cytotoxic, antidiabetic, etc.) found in extracts and isolated compounds of 38 Neotropical sages. From extracts of these species, a total of 110 compounds have been isolated, identified and evaluated pharmacologically; 72 of these compounds are clerodanes, 23 abietanes, six flavonoids, five sesquiterpenoids, and four triterpenoids. The most characteristic metabolites found in the Neotropical sages are the diterpenes, particularly clerodanes (e.g., Amarisolide A, Tilifodiolide), that are found almost exclusively in this group, and were likely acquired during its evolutionary history. The Neotropical sages are a promising resource in the production of herbal medication, but studies that corroborate the properties that have been attributed to them in traditional medicine are scarce. Research of these metabolites guided by the phylogenies is recommended, since closely related species tend to share the presence of similar compounds and thus similar medicinal properties.